Atlas of Cardiovascular Computed Tomography (Springer London, 2018)
This atlas is a comprehensive visual reference for the use of cardiovascular computed tomography (CT) containing photomicrographs, anatomic illustrations, tables, and charts paired with extensive legends and explanations that are supplemented by extensive research, peer-reviewed articles, and textbooks. In addition to providing historical perspective and current direction for CT, this new edition of Atlas of Cardiovascular Computed Tomography 2e focuses on research involving coronary artery diseases and anomalies, congestive heart failure, atherosclerotic plaques and asymptomatic disease, as well as imaging techniques, including preparation, acquisition, and processing, involving the great vessels and carotids, the peripheral vasculature, and coronary and pulmonary veins. The increasing role of CT in the emergency room and in private cardiology practice is also reviewed thoroughly, making this an essential read for all involved in cardiac imaging, cardiology and emergency medicine.